Development of the Gastronomic Attraction of the Bedulang Eating Tradition in the Traditional House of Belitung Regency - Yunisti Pratiwi; Syahrul Syahrul (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2023)
The purpose of this research is to find out the history, philosophy and tradition of eating bedulang, as well as to find out how the development strategy is to become a gastronomic tourist attraction in Belitung Regency by being located in the traditional house of Belitung Regency. The type of research used is qualitative with interview, observation and documentation methods. The results of this study will describe the history of the philosophy and development strategy undertaken with the hope that this effort can make it a tourist attraction, especially gastronomy that attracts and is of interest to tourists.